Dynamic features descriptor for road user recognition using hierarchal graph dynamic gradient pattern - Al-Smadi M.; Abdulrahim K.; Salama R.A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by SCOPUS